2021
DOI: 10.1086/712378
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Male-Male Interference during Dispersal of Orchid Pollen

Abstract: Siring success of flowering plants depends on the fates of male gametophytes, which compete for access to stigmas, stylar resources and ovules. Although rarely considered, pollen may often compete during dispersal, affecting the processes required for export to stigmas; pollen pickup, transport and deposition. We quantified dispersal interference by tracking bee dispersal of stained Anacamptis morio (Orchidaceae) pollen from individual donor flowers and inferred the affected dispersal mechanisms based on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…There is, however, evidence to suggest that pollen packaged in pollinaria may generate structured pollen landscapes on pollinators, which may result in competition between individuals (Cocucci et al, 2014; Duffy and Johnson, 2014; Harder et al, 2021). For example, Harder et al (2021) demonstrated that the presence of pre‐existing pollinaria on bee pollinators reduced the export of pollen from subsequently visited flowers by 27%. Cocucci et al (2014) also found evidence that the pollinaria of some milkweed species have horns that prevent or preclude the attachment of pollinaria from subsequently visited flowers.…”
Section: Figurementioning
confidence: 99%
“…There is, however, evidence to suggest that pollen packaged in pollinaria may generate structured pollen landscapes on pollinators, which may result in competition between individuals (Cocucci et al, 2014; Duffy and Johnson, 2014; Harder et al, 2021). For example, Harder et al (2021) demonstrated that the presence of pre‐existing pollinaria on bee pollinators reduced the export of pollen from subsequently visited flowers by 27%. Cocucci et al (2014) also found evidence that the pollinaria of some milkweed species have horns that prevent or preclude the attachment of pollinaria from subsequently visited flowers.…”
Section: Figurementioning
confidence: 99%
“…Empirical studies that assess pollen transfer and delivery require tracking the movement of individual pollen grains (Minnaar et al 2019). Given the difficulty to achieve this pollen-level resolution in practice, empirical studies are often restricted to species that present trackable pollen grains either because they are aggregated in pollinaria (Johnson and Harder 2018; Harder et al 2021), or because they can be distinguished by size and color polymorphisms (Thomson 1986; Harder and Thomson 1989; Luo et al 2008; Wang et al 2018). Other studies have observed pollen transfer by staining techniques with fluorescent powders (Lertzman 1981; Price and Waser 1982; Waser and Price 1984) or quantum dots (Minnaar and Anderson 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Tritoniopsis antholyza female-phase flowers develop first, in the bottom of plant and are typically visited by sunbirds before the male-phase flowers, which develop after and on top of the plant. Harder et al (2021) already registered similar behavior for bee pollinators, which usually visit flowers from the bottom upwards, visiting first the female flowers and then the male flowers. While this is known to reduce geitonogamy (Harder et al, 2000), it may also increase pollen export if the female -phase flowers clean pre-existing pollen from rival individuals, allowing the male -phase flowers to place pollen onto relatively pollen-free pollinators.…”
Section: Discussionmentioning
confidence: 81%
“…Pollen smothering may occur when flowers are able to cover pre-existing pollen from previous visits, so their pollen has a higher probability of reaching the stigma of subsequently visited flowers . Pollen preclusion may occur when pre-existing pollen loads prevent or preclude the deposition of new pollen grains onto pollinators (Harder et al, 2021). In pollen preclusion, we could expect that the amount of pollen deposited onto a pollinator will be inversely proportional to the amount of pre-existing pollen on that pollinator (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation